ECO-FRIENDLY TECHNOLOGIES AND ITS EFFECTS - shrivastava, Pratibha (International Journal of Research -GRANTHAALAYAH, 2015)
Eco-friendly technologies involved making use of alternative energy source which is abundant to generate renewable energy, reducing the amount of resource which is limited used through the conventional like fossil fuel. For example renewable resources like sunlight, sea water and co2 which are abundant generating alternative resource like biofuel, solar energy, freshwater and air purification through greenhouse, vegetation and halophytes cultivation stabilize the degraded desert soil and as wind breaks reduce the impact of pollutants on the environment.